Immobilization studies of Candida Antarctica lipase B on gallic acid resin-grafted magnetic iron oxide nanoparticles - SreeHarsha, Nagaraja; Ghorpade, Ravindra, V.; Alzahrani, Abdullah Mossa; Al-Dhubiab, Bandar E.; Venugopala, Katharigatta N. (International Journal of nanomedicine, 2019)
Purpose: Here, we present the successful preparation of a highly efficient gallic acid resin grafted with magnetic nanoparticles (MNPs) and containing a branched brush polymeric shell. Methods: Using a convenient co-precipitation method, we prepared Fe3O4 nanoparticles stabilized by citric acid. These nanoparticles underwent further silica modification and amino functionalization followed by gallic acid functionalization on their surface. Under alkaline conditions, we used a condensation reaction that combined formaldehyde and gallic, to graft the gallic acid-formaldehyde resin on the surface. We then evaluated the polymer-grafted MNPs to assay the Candida Antarctica B lipase(Cal-B) immobilization via physical adsorption. Conclusion: Furthermore, during optimization of parameters that defined conditions of immobilization, we found that the optimum immobilization was achieved in 15 mins Also, optimal immobilization temperature and pH were 38 degrees C and 7.5, respectively. In addition, the reusability study of immobilized lipase polymer-grafted MNPs was done by isolating the MNPs from the reaction medium using magnetic separation, which showed that grafted MNPs reached 5 cycles with 91% activity retention.